KAJIAN LAJU INFILTRASI PADA LERENG YANG TERTUTUP ABU VULKANIK BERDASARKAN EKSPERIMEN SKALA LABORATORIUM - Nugroho, Joko; Soekarno, Indratmo; Yunita, F Tata; Kuntoro, Arno Adi (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2022)
Indonesia has 129 active volcanoes; therefore, the volcanic-related disasters risk is relatively high. Lahar flood is a secondary post-eruption disaster, which is triggered by the rainfall due to the movement of volcanic material by the runoff. After the eruption, there will be some significant changes in the watershed characteristics, especially the land cover, slope, and eruption material. This condition increases the possibility of the lahar flood events. Several studies have indicated an increase in runoff due to volcanic ash deposits on slopes. In this regard, the aim of this research is to understand the effects of volcanic ash layer on the slope on the infiltration rate. The physical model laboratory in the form of a laboratory-scale demonstration plot (demplot) were used, where the parameters reviewed include the slope, the volcanic ash thickness, and the rainfall intensity. The results indicate that the infiltration rate on the slopes covered with volcanic ash decreases with the average decrease in the ratio of infiltration to total rainfall about 1.6% per 1 cm thickness of the volcanic ash layer. In addition, the decrease in infiltration rate per 1 cm thickness of volcanic ash on a slope with a slope of 80 was higher (2.3%), compared to a slope of 150 (0.7%). The Philip's infiltration model fits better with the actual measurement data than the Green-Ampt one. The significant parameter in influencing the infiltration rate of the volcanic ash layer with Philip's model based on sensitivity analysis is sorptivity.Keywords: Infiltration rate, Philip, Green-Ampt, volcanic ash, physical model test